2011
DOI: 10.1002/pon.1979
|View full text |Cite
|
Sign up to set email alerts
|

Whether, when, and who to disclose bad news to patients with cancer: a survey in 150 pairs of hospitalized patients with cancer and family members in China

Abstract: There was poor or slight concordance in disclosure preferences between patients with cancer and their families. More patients than their families wanted to be informed completely, immediately, and directly by doctors. Farmer patients with cancer were less likely to prefer to be informed completely, immediately, and directly by doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
1
30
2
2
Order By: Relevance
“…The outcome that more cancer patients than family caregivers prefer to be informed of their poor prognosis including terminal illness and short life expectancy not only prevails in the Asian culture but was also reported in the USA and Europe . Our study showed that there was substantial discrepancy in poor‐prognosis disclosure preference between the patient group (90%) and the family group (61.2%).…”
Section: The Current Situation Of Cancer Patients' and Caregivers' Pomentioning
confidence: 54%
See 1 more Smart Citation
“…The outcome that more cancer patients than family caregivers prefer to be informed of their poor prognosis including terminal illness and short life expectancy not only prevails in the Asian culture but was also reported in the USA and Europe . Our study showed that there was substantial discrepancy in poor‐prognosis disclosure preference between the patient group (90%) and the family group (61.2%).…”
Section: The Current Situation Of Cancer Patients' and Caregivers' Pomentioning
confidence: 54%
“…However, more matched caregivers in the III–IV stage subgroup than in the I–II stage group preferred to withhold poor prognosis (70.1% vs. 58.5%); such a change in caregivers' preference might have originated from Chinese Confucianism and the widespread beneficence principle . Physicians should therefore note that there is a discrepancy between cancer patients' and their caregivers' disclosure preferences . Moreover, the caregivers whose relative patients were in III–IV stage should be provided with adequate ongoing guidance about practical facets of care skills and effective ways to communicate with patients .…”
Section: The Current Situation Of Cancer Patients' and Caregivers' Pomentioning
confidence: 99%
“…Therefore, we suggest that physicians attempt to satisfy patients' desire for disclosure of the diagnosis. However, for patients who are not prepared to accept the cancer condition, physicians should provide additional psychological support and wait until the time is right before disclosing the diagnosis, although this situation represented the smaller proportion of patients (69 out of 218 in our study) in the clinical setting .…”
Section: Discussionmentioning
confidence: 94%
“…This is most likely because for the patients who desired to know the truth about their illness, telling the truth may seem more in concordance with their coping style and might positively influence the effectiveness of their coping strategies . However, for the patients who did not want disclosure of the diagnosis, their attitudes implied that they were not prepared to accept the cancer diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Çin'de yapılan bir çalışmada beklenenin aksine hastaların (%98'i) kendilerine doğrudan ve hekim tarafından, hastalıkları ile bilginin verilmesini istedikleri bulunmuştur (23). Ülkemizde yürütülen bir çalışma-da 151 hekim ve 150 hastaya anket uygulanmış ve verilen önermelere katılıp katılmadıkları sorulmuştur.…”
Section: A) Yaşam Sonu Kararlarıunclassified